2013
DOI: 10.1158/0008-5472.can-13-0358
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-218 Inhibits Glioma Invasion, Migration, Proliferation, and Cancer Stem-like Cell Self-Renewal by Targeting the Polycomb Group Gene Bmi1

Abstract: Malignant gliomas are the most common central nervous system tumors and the molecular mechanism driving their development and recurrence is still largely unknown, limiting the treatment of this disease. Here, we show that restoring the expression of miR-218, a microRNA commonly downregulated in glioma, dramatically reduces the migration, invasion, and proliferation of glioma cells. Quantitative reverse transcription PCR and Western blotting analysis revealed that expression of the stem cell-promoting oncogene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
158
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(171 citation statements)
references
References 44 publications
12
158
0
1
Order By: Relevance
“…Glioma is a diffuse and highly-invasive tumor, resulting in a dismal prognosis, and long-term survivors are rare (3). Gliomas are also characterized by high migratory and proliferative abilities (4). However, the molecular mechanism that triggers the development of gliomas is elusive and requires additional investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Glioma is a diffuse and highly-invasive tumor, resulting in a dismal prognosis, and long-term survivors are rare (3). Gliomas are also characterized by high migratory and proliferative abilities (4). However, the molecular mechanism that triggers the development of gliomas is elusive and requires additional investigation.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, miR-21 acts as an antiapoptotic factor in GBM by targeting the p53 network (8 -10); miR-10b is involved in the cell cycle and programmed cell death via regulating the expression of Bim, TFAP2C, p16, and p21 (11); miR-218 inhibits cell migration, invasion, proliferation, and stem-like qualities by targeting Bmi1 (12); miR-195 negatively regulates the proliferation of glioma cells by down-regulating the expression of cyclin D1 and cyclin E1 (13); miR-137 inhibits the growth of glioma cells by directly targeting Rac1 (14); and miR-16 functions as a tumor suppressor gene in glioma growth and invasiveness via the inhibition of BCL2 and the NF-KB1/MMP-9 signaling pathway (15). All of these miRNAs play important roles in the development of the malignant GBM phenotype.…”
mentioning
confidence: 99%
“…Interestingly, tumor-suppressive microRNA-218 inhibits cancer cell migration and invasion via targeting of LASP1 in prostate cancer (Nishikawa et al, 2014). It was also found that miR-218 could inhibit migration and invasion in other human cancers by targeting multiple mRNAs, including glioma (Yamamoto et al, 2013;Yamasaki et al, 2013;Tu et al, 2013). The emerging role of tumor-suppressive microRNA-218 in targeting glioblastoma stemness is also reported (Gao X and Jin W, 2014).…”
Section: Discussionmentioning
confidence: 90%
“…Recently, microRNA-218 (miR-218) has been reported to serve as a tumor suppressor in numerous types of cancer by regulation of the expression of target genes. In glioma, miR-218 could inhibit glioma invasion, migration, proliferation, and cancer stem-like cell selfrenewal by targeting the polycomb group gene Bmi1 (Tu et al, 2013). Also, miR-218 acts as a tumor suppressor by targeting multiple cancer phenotype-associated genes in medulloblastoma (Venkataraman et al, 2013).…”
Section: Expression Of Microrna-218 and Its Clinicopathological And Pmentioning
confidence: 99%